2018
DOI: 10.1055/s-0038-1646776
|View full text |Cite
|
Sign up to set email alerts
|

Bite Force Assessment of Mandibular Interforaminal Fractures Treated with Combination of Microplate and Miniplate—A Randomized Control Study

Abstract: Trauma to the facial skeleton frequently results in injuries to the soft tissues, teeth, and major skeletal component of the face, including mandible, maxilla, zygoma, naso-orbito-ethmoid complex, and supra orbital fractures. 1Proper anatomical reduction, restoration of the premorbid occlusion, and proper fixation until stable osseointegration are considered as the basic principles in treating mandibular fractures. Miniplates and reconstruction plates are commonly used to treat simple and comminuted fractures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…Sadove and Eppley,[ 41 ] Gupta et al .,[ 42 ] Xie et al .,[ 43 ] Huston and Stassen (2016)[ 44 ] Anand et al ., Abdullah (2009), Ozkan and Cil, Anand et al . [ 45 ] found no significant difference among their study groups for fractures treated with microplates in terms of infection and plate exposure. Burm et al .…”
Section: Discussionmentioning
confidence: 99%
“…Sadove and Eppley,[ 41 ] Gupta et al .,[ 42 ] Xie et al .,[ 43 ] Huston and Stassen (2016)[ 44 ] Anand et al ., Abdullah (2009), Ozkan and Cil, Anand et al . [ 45 ] found no significant difference among their study groups for fractures treated with microplates in terms of infection and plate exposure. Burm et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, the forces achieved at the end of 3 months at the incisor, premolar and molar regions were not completely normal, considering that the average bite forces are 22-50 kgs at the molars, 15-40 kgs at the premolars and 3-27 kgs at the incisors in healthy individuals without a fracture. 7,9,17 Throckmorton and Ellis 18 found that surgical correction of unilateral condylar fractures has relatively little effect on the duration and excursion of masticatory function. In the current study, by the end of 3 months, those patients treated with ORIF had significantly higher bite forces than those managed with the closed method, and they also had relatively fewer occlusal discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were observed in the current study with a significant increase in the bite forces from the pre‐operative to 1 week, 1 week to 1 month and 1 month to 3 months post‐operative periods. However, the forces achieved at the end of 3 months at the incisor, premolar and molar regions were not completely normal, considering that the average bite forces are 22–50 kgs at the molars, 15–40 kgs at the premolars and 3–27 kgs at the incisors in healthy individuals without a fracture 7,9,17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The OSMF patients were graded according to the previous classification. The patients were divided into four groups on the basis of interincisal mouth opening, i.e., group I (mouth opening, 35 mm), group II (mouth opening between 30 and 35 mm), group III (mouth opening between 20 and 30 mm), and group IV (mouth opening, 20 mm) [ 14 ]. The inclusion criteria considered in the selection of the participant are as follows: angle class I molar relationship without an anterior or posterior crossbite or open bite; class 1 facial profile and normal facial height and no history of orthodontic therapy; no missing teeth in the molar region; no pain related to the molars; no heavily restored teeth in the molar region; no gingival inflammation, no periodontal pathology, and absence of mobility of the teeth; and no reported systemic disease (chronic arthritis) or apparent facial asymmetry that could influence the registration of bite force.…”
Section: Methodsmentioning
confidence: 99%